Gender differences in arrhythmias and psychological discomfort management. (19th May 2022) - Giaccardi, M; Strisciuglio, T; Turreni, F; Marinigh, R; Carreras, G; Pelargonio, G; Bisceglia, C
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Palpitations and/or syncope are common in patients with psychoneurological disorders [1]. Arrhythmias may be associated to psychological discomfort as well [2]. Psychiatrics, epidemiology and commonplace agree that gender may lead to difference in symptom perception, and management [3-4] Purpose: To investigate the abovementioned association we realized a retrospective multicentric registry including, after definite instrumental diagnosis, patients with previous mental disorder diagnosis, referring to arrhythmology ambulatories. Results: 64 pts (48 F, 75%), mean age 54±18y, were enrolled in 7 centers. Psychiatric diagnoses were: anxiety-depression disorder (N=50), panic attack (N=5), behavioural disorder (N=4), epilepsy (N=3), psychosis (N=1), diagnosed in 83% by General Practitioners and in 14% by Psychiatrists. 55 pts (86%) were on drug therapy: benzodiazepines (67%), SSRI (22%), neuroleptics (3%), antidepressants (2%), and natural products (5%). Among these, 89% reported no symptoms relief. 57 pts complained palpitations, 17 extrasystoles and 19 reported syncope. EPS study was performed in 48%, 24 h Holter ECG in 28%, and LR implantation in 5% of patients. We diagnosed AF (N=11), typical AFL (N=4), AT (N=8), AVNRT (N=16), AVRT (N=4), PAC (N=1), PVC (N=10), AV block (N=4), VT (N=3) and unspecified SVT (N=3). 44 pts underwent ablation. 62 pts (96, 8) experienced strong symptoms reduction or resolution, and 42 psychiatric drugs withdrawal. One pt underwent PMK implantation. Conclusions: In our series of cardiac symptoms ascribed to psychiatric disorders, women markedly prevailed. Psychologic discomfort could be caused by arrhythmias, as resolved or dramatically ameliorated by diagnosis and treatment. Further investigation in Psychiatric context is warranted.